Kava for generalised anxiety disorder: A 16-week double-blind, randomised, placebo-controlled study. (March 2020) - Sarris, Jerome; Byrne, Gerard J; Bousman, Chad A; Cribb, Lachlan; Savage, Karen M; Holmes, Oliver; Murphy, Jenifer; Macdonald, Patricia; Short, Anika; Nazareth, Sonia; Jennings, Emma; Thomas, Stuart R; et al.
Objective: Previous randomised, double-blind, placebo-controlled studies have shown that Kava (a South Pacific medicinal plant) reduced anxiety during short-term administration. The objective of this randomised, double-blind, placebo-controlled study was to perform a larger, longer-term trial assessing the efficacy and safety of Kava in the treatment of generalised anxiety disorder and to determine whether gamma-aminobutyric acid transporter (SLC6A1) single-nucleotide polymorphisms were moderators of response. Methods: The trial was a phase III, multi-site, two-arm, 16-week, randomised, double-blind, placebo-controlled study investigating an aqueous extract of dried Kava root administered twice per day in tablet form (standardised to 120 mg of kavalactones twice/day) in 171 currently non-medicated anxious participants with diagnosed generalised anxiety disorder. The trial took place in Australia. Results: An analysis of 171 participants revealed a non-significant difference in anxiety reduction between the Kava and placebo groups (a relative reduction favouring placebo of 1.37 points; p = 0.25). At the conclusion of the controlled phase, 17.4% of the Kava group were classified as remitted (Hamilton Anxiety Rating Scale score < 7) compared to 23.8% of the placebo group ( p = 0.46). No SLC6A1 polymorphisms were associated with treatment response, while carriers of the rs2601126 T allele preferentially respond to placebo ( p = 0.006). Kava was well tolerated aside from poorer memory (Kava = 36 vs placebo = 23; p = 0.044) and tremor/shakiness (Kava = 36 vs placebo = 23; p = 0.024) occurring more frequently in the Kava group. Liver function test abnormalities were significantly more frequent in the Kava group, although no participant met criteria for herb-induced hepatic injury. Conclusion: While research has generally supported Kava in non-clinical populations (potentially for more 'situational' anxiety as a short-term anxiolytic), this particular extract was not effective for diagnosed generalised anxiety disorder.